ORANG KALANG, CINA, DAN BUDAYA PASAR DI PEDESAAN JAWA - Mulyanto, Dede (Jurnal Masyarakat dan Budaya, 2015)
his essay is a preliminary analysis on social condition of Chinese people as well as the Kalang of Java in relation to their social identity as ‘merchant family’. Both of them are minority groups of people in rural Java. Though ethnographical research in a Javanese village in Banyumas District, Central Java for four months, I realised that the Chinese and the Kalang are identified by the Javanese as ‘merchant family’ based on ‘market-place culture’ (budaya pasar). Accordingly, market-place culture can be defined as collective way of life that placed local trading activity and livelihood as a main socio-economic orientation of the family. Meanwhile, the Javanese, as dominant ethnic group in the village, see themselves and been seen by Chinese and the Kalangs as thani or traditional land cultivator who hold ‘land-culture’ (budaya lahan) as their main socio-economic orientation. Among their Javanese neighbours, the Chinese and the Kalangs’ social identity is accepted through reproducing their myth of origin and to differentiate their group norms and values.